PENERAPAN METODE DRILL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 001 JAPURA KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU - Dewi Apriani; Eddy Noviana; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this research is based on the fact that happened in class V SD Negeri 001 Japura, who showed symptoms of low ability to absorb students in math. The problem of this research is "Does the application of methods drill can improve learning outcomes math class V students of SD Negeri 001 Japura District of Lirik Indragiri Hulu?" The purpose of this research is to improve learning outcomes math class V students through the application of methods drill in SD Negeri 001 Japura Lirik Indragiri Hulu subdistrict. This study took place in class V SD Negeri 001 Japura District of Lirik and executed April 13 until April 29th 2016, with the number of subjects as many as 20 people consisting of 11 girls and 9 boys. This research is a classroom action research conducted in two cycles. Based on the results the percentage learning outcomes on the basis of the average score increased in Deuteronomy 60 Daily I became 72, with an increase of 20%. In Deuteronomy Daily II increased to 80 with an increase of 11.1%. Then of completeness individual and classical, in the first cycle the number of students who pass as many as 11 people of 55% and an incomplete 9 by 45%, in the second cycle the number of students who completed 18 of 90%, while the incomplete 2 of 10%. From these results demonstrate the applicability of the drill method can improve learning outcomes in mathematics V SDN 001 Japura District of Indragiri Hulu Lirik academic year 2015/2016.Keywords: Drill Method, Results Learning, Mathematics